The rocky road to success - Collins, D.; MacNamara, A. (Talent development: A practitioner guide, 2018)
The majority of Talent Development (TD) systems try to smooth the pathway for young athletes and expend a great deal of effort, and resources, maximising and trying to counter the impact of naturally occurring life stressors. In this chapter we suggest that a degree of challenge, the inclusion of structured challenges designed and implemented as part of the TD pathway, is not only desirable but essential to eventual high-level performance. This chapter provides guidelines about the purposeful provision of such challenge at appropriate levels of the TD system. We explore how such challenges can be built into the TD pathway along with implications for the design and conduct of optimum academies and TD environments. Central to the success of this approach is the proactive teaching, supported deployment, then facilitated reflection of the skills needed to cope with the `ups and downs` of development; such development should not just be left to chance or the serendipity of supportive home backgrounds. Finally, implication for this `rocky road` approach for parents, as key stakeholders and influencers in this process, are presented and discussed.